Membangun Semangat Belajar dan Nasionalisme dengan Memperkenalkan Budaya Indonesia di Sanggar Bimbingan Kuala Langat: Inculcating a Spirit of Learning and Nationalism through the Introduction of Indonesian Culture at the Sanggar Bimbingan Kuala Langat - Miranti, Dyah; Astutik, Atika Fitri; Rahmawati, Nadia Putri (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This article is the result of Community Service Activities, which are a form of implementation of KKN-Dik batch 5 and a form of participation to help fulfill the educational rights of the children of Indonesian Migrant Workers (PMI) in Malaysia as stated in the 1945 Constitution